2003
DOI: 10.1111/j.1467-842x.2003.tb00414.x
|View full text |Cite
|
Sign up to set email alerts
|

The Year of the Salmonella Seekers—1977

Abstract: In 1977 two major outbreaks of salmonella infection originated in Victoria. The first of these, involving Salmonella Bredeney, continued over some seven months and was traced to contamination of powdered milk‐based infant formulae during manufacture. This caused cases of gastroenteritis among young children throughout Australia. Another incident led to the discovery that salmonella serovars were colonising not one, but a number of dairy factories through the State. The second outbreak was of typhoid, stemming … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…In Trinidad, in 1973, salmonellosis was an island-wide outbreak and, as a result, Salmonella derby infected 3000 infants (Weissman et al, 1977). In Australia, in 1977, Salmonella bredeney caused a major outbreak of salmonellosis due to consumption of contaminated powdered milk infant formulae during manufacture (Forsyth et al, 1977). In USA, salmonellosis among infants is eight times more common than among other age groups (Skirrow, 1987).…”
Section: Salmonellamentioning
confidence: 99%
“…In Trinidad, in 1973, salmonellosis was an island-wide outbreak and, as a result, Salmonella derby infected 3000 infants (Weissman et al, 1977). In Australia, in 1977, Salmonella bredeney caused a major outbreak of salmonellosis due to consumption of contaminated powdered milk infant formulae during manufacture (Forsyth et al, 1977). In USA, salmonellosis among infants is eight times more common than among other age groups (Skirrow, 1987).…”
Section: Salmonellamentioning
confidence: 99%
“…Based on the reports found, there were 407 cases of Salmonella infant infection from twelve unrelated outbreaks that could be attributed to contaminated PIF in the past 50 years. From the compiled data, one was fatal (0•2 %) (Table 4 [103][104][105][106][107][108][109][110][111][112][113][114] ). These morbidity and mortality rates for Salmonella infection from contaminated PIF may well represent a substantial under-reporting.…”
Section: Risks Associated With Powdered Infant Formulamentioning
confidence: 99%
“…All outbreaks of Salmonella infections caused by contamination of PIF were either traced back to manufacturing equipment or the raw milk product (103,105,106,109,116,117) or isolated from unopened tins of PIF, implicating the manufacturing environment. The only exception was an outbreak in a neonatal intensive care unit in 2001, which was attributed to infected staff (108) .…”
Section: Exposure Effectsmentioning
confidence: 99%
“…IDF, 1991b; Burgess et al, 1994) and the implementation of HACCP have greatly contributed to improvements. Nevertheless, outbreaks in different countries are reported from time to time, including dairy based infant formulae, which are manufactured in a similar way (Becker and Terplan, 1986;Rowe et al, 1987;Gelosa, 1994;Usera et al, 1996;Anonymous, 1997a;Threlfall et al, 1998;Bornemann et al, 2002;Forsyth et al, 2003). These outbreaks demonstrated that failures in preventive systems, such as presence of water allowing multiplication of salmonellae, or zones that are difficult to maintain and to clean (isolation from a drying tower), were the origin of contamination, and that salmonellae with particular characteristics (lactose positive) were involved.…”
Section: Pathogensmentioning
confidence: 99%